Institute of Petitions in Criminal Procedural Law: A Comparative Legal Analysis - X.Z. Kudratillaev (Scientific Trends, 2026)
The article provides a comprehensive comparative legal analysis of the institute of petitions in criminal procedural law. Petitions, including applications, motions, and complaints, are examined as an independent procedural institution ensuring access to justice, protection of individual rights, and effective judicial control. The research is based on a comparative study of the criminal procedure legislation and judicial practices of Germany, France, and the Russian Federation, as well as the standards developed by the European Court of Human Rights. The article identifies conceptual differences in the legal nature, scope, and procedural guarantees of petitions and substantiates proposals for improving national criminal procedural legislation in line with international standards.
Keywords: Criminal procedure; petitions; applications; motions; complaints; comparative legal analysis; procedural guarantees; access to justice.